Sunday

March 1, 2015

March 1, 2015

Posted by **Betty** on Tuesday, February 22, 2011 at 11:56am.

-3x – 5y = 61

7x – 5y = -9

- Algebra -
**Henry**, Thursday, February 24, 2011 at 3:49pmEq1: -3X - 5Y = 61

Eq2: 7X - 5Y = -9

Multiply both sides of Eq1 by -1 and

add the 2 Eqs:

3X + 5Y = -61

7X - 5Y = -9

Sum: 10X = -70,

X = -70 / 10 = -7.

Substitute -7 for x in Eq2:

7*-7 - 5Y = -9,

-49 - 5Y = -9,

-5Y = -9 + 49 = 40,

Y = 40 / -5 = -8.

Solution set = (-7, -8).

**Answer this Question**

**Related Questions**

algebra - Solve using the elimination method. Show your work. If the system has ...

algebra - Solve using the elimination method. Show your work. If the system has ...

algebra - Solve using the elimination method. Show your work. If the system has ...

algebra - solve using the elimination method. show your work. if the system has ...

algebra - Solve using the elimination method. Show your work. If the system has ...

algebra - Solve using the elimination method. Show your work. If the system has ...

algebra - Solve using the elimination method. Show your work. If the system has ...

Algebra - Solve using the elimination method. Show your work. If the system has ...

Algebra - Solve using the elimination method.Show work.If the system has no ...

intermediate algebra - Solve using the elimination method. Show your work. If ...